Site Dance : Choreographers and the Lure of Alternative Spaces - Pavlik, Carolyn; Kloetzel, Melanie (Book collections on Project MUSE., 2009)
This anthology examines site-specific dance. The editors Melanie Kloetzel and Carolyn Pavlik, explore the work that choreographers create for nontraditional performance spaces and the thinking behind their creative choices.